Elements of the Formal Procedures in Zaum Poetic Experiment - Latifić, Amra (Poznańskie Studia Slawistyczne, 2017)
The paper analyzes the elements and strategies of Russian formalism applied to the Russian avantgarde zaum poetic experiment of Alexei Kruchenykh and Viktor Khlebnikov. In futuristic tendencies to create a trans-rational language or zaum language lies the idea of a new voice, sounds and semantic meaning. According to Russian poets the new semantic meaning of the word is obtained only in the process of performing a poem. Also, according to Russian formalism, sound of poem, in the performing process, has its own independent meaning. In this sense zaum experiment in its printed form does not possess a fixed resolution of meanings, but only has potential of meanings. The function of fixed forms, that during the process of performing is to form a new movable semantic meaning.